FPGA-Based Real-Time Digital Solver for Electro-Mechanical Transient Simulation - Bingda Zhang; Yang Wang; Sijia Tu; Zhao Jin (Energies, 2018)
A field-programmable gate array (FPGA)-based digital solver for real-time electromechanical transient simulation is designed in this paper. The solving process for a device or sub-network in an electromechanical transient simulation is packaged into the orders in soft function solvers. The orders are reused by soft function solvers that are invoked by microprocessor cores. The data exchange between the microprocessor cores and soft function solvers is enhanced through explicit and implicit channels. The orders of the microprocessor cores are stored in the synchronous dynamic random access memory on the FPGA board, which solves the problem of insufficient storage space for the orders in electromechanical transient simulation. A real-time digital solver for electromechanical transient simulation, whose feasibility is verified by a simulation of part of the power system in East China, is successfully constructed by applying a small number of microprocessor cores and multiple soft function solvers.